Electricity trade and cooperation in the BBIN region: lessons from global experience. Issue 3 (4th May 2021) - Vaidya, Ramesh Ananda; Yadav, Niru; Rai, Nirjan; Neupane, Saumitra; Mukherji, Aditi
ABSTRACT: The acute shortage of electric power in South Asia has severely hampered regional economic growth. Cross-border electricity trade – supported by appropriate policies, institutions and grid interconnections – can be a powerful tool for improving people's livelihoods in its Bangladesh–Bhutan–India–Nepal (BBIN) region. This paper reviews four cases of regional power trade and cooperation from four different continents – Asia, Africa, Latin America and Europe – and identifies six key elements that will be necessary for success in cross-border electricity trade in the BBIN region. It assesses the current status of these key elements in the BBIN countries and suggests areas for immediate intervention. Cooperation in the electricity sector in the region could be the building block for a larger regional cooperation in South Asia – and ultimately for regional economic integration.